A rare case of pleural effusion due to Acinetobacter junii in a known patient of pulmonary tuberculosis - Kilikdar, Mousumi; Ambhore, Nitin A.; Shekokar, Divya S.; Karyakarte, Rajesh P. (International Journal of Research in Medical Sciences, 2018)
The genus Acinetobacter comprises a heterogenous group of bacterias that are mostly pandrug resistant and implicated in variety of nosocomial infections. Acinetobacter junii is a rare human pathogen and is mainly associated with blood stream infections in paediatric oncology patients. We report a rare case of pleural effusion caused by A. junii in a known pulmonary tuberculosis patient who was on cat-1 antitubercular treatment.